Reducing the risk of prenatal alcohol exposure and FASD through social services: promising results from the FAR SEAS pilot project - Okulicz-Kozaryn, Katarzyna; Segura-García, Lidia; Bruguera, Carla; Braddick, Fleur; Zin-Sędek, Marta; Gandin, Claudia; Słodownik-Przybyłek, Luiza; Scafato, Emanuele; Ghirini, Silvia; Colom, Joan; Matrai, Silvia (Frontiers in Psychiatry, 2023)
1) Introduction. Within FAR SEAS, a multi-component evidence-based community intervention was implemented and evaluated in Mazovia (Poland), with the aim of preventing alcohol-exposed pregnancies, and therefore preventing FASD. (2) Method. Multi-disciplinary professionals from different services (social, addiction, and psychology), recruited women of child-bearing age (pregnant and not pregnant) in local communities, screened them for alcohol risk, and allocated participants (n=441) to groups for low-(70%), moderate-(23%) or high-risk (7%) of alcohol exposed pregnancy, to provide interventions tailored to their needs. The non-parametric sign test, testing differences between pairs of observations before and after intervention was used to evaluate the outcomes. (3) Results. Follow-up data (collected from 93% of participants) indicated positive changes in the key outcome variables: risky alcohol consumption dropped by 81%, contraception use increased by 15% and visiting a gynecologist increased by 39%; as well as in associated psychosocial risk factors (decrease in cigarette and drug use, domestic violence and depressive symptoms). No changes were noted in frequency of other service use (medical, psychological or social). The most prominent changes were observed in the moderate-risk group. (4) Discussion. Changing risky behaviors